Comparison of Ocular Surface Cytological Appearance in Glaucoma Patient Treated with Timolol Maleat 0,5% Latanoprost 0,005% and Timolol-Latanoprost Fixed Combination Preservative Free Eye Drop - Maretha Amrayni; Elsa Gustianty; Susi Heryati; Andika Prahasta; Maula Rifada; Hasrayati Agustina (Majalah Oftalmologi Indonesia, 2018)
Introduction : The longterm use of topical antiglaucoma might cause ocular surface instability due to active substance or preservative used. Impression cytology examination may reveal superficial epithelial cells on conjunctiva and cornea, including goblet cells. Goblet cell density decrease is the most important parameter on evaluation of ocular surface disorder. Objective : This study was to understand ocular surface remodeling due to active substance of topical antiglaucoma with impression cytology examination among the patient prior and 3 months after therapy. Methods : This was a randomized controlled trial study with single blind masking. A total of 45 eyes from 31 patients were used as subject and distributed onto three groups treatment, which were timolol maleat 0.5%, latanoprost 0.005%, and latanoprost-timolol maleat fixed combination. All topical antiglaucoma in this study were preservative free. Result : There were differences between 3 groups in goblet cells density after 3 months therapy (p=0,030). Goblet cell density in timolol group was lower than latanoprost (p=0,041) and fixed combination (p=0,045). There was no significantly difference between 3 groups in conjunctival epithelial metaplasia degree (p=0,706) and cell to cell contact degree in corneal epithelial cells (p=0.66) after 3 months therapy. Conjunctival epithelial metaplasia degree were increased among group of timolol (p=0,008) and fixed combination (p=0,046). Conclusion : Timolol maleat 0,5% caused lower goblet cell density after 3 months therapy compare with latanoprost and fixed combination. There was no significantly difference in conjunctival epithelial metaplasia and cell to cell contact degree in corneal epithelial cells among these glaucoma treatment groups.